Design of Engineered Elastomeric Substrate for Stretchable Active Devices and Sensors. (27th May 2018) - Cantarella, Giuseppe; Costanza, Vincenzo; Ferrero, Alberto; Hopf, Raoul; Vogt, Christian; Varga, Matija; Petti, Luisa; Münzenrieder, Niko; Büthe, Lars; Salvatore, Giovanni; Claville, Alex; Bonanomi, Luca; et al.
Abstract: In the field of flexible electronics, emerging applications require biocompatible and unobtrusive devices, which can withstand different modes of mechanical deformation and achieve low complexity in the fabrication process. Here, the fabrication of a mesa‐shaped elastomeric substrate, supporting thin‐film transistors (TFTs) and logic circuits (inverters), is reported. High‐relief structures are designed to minimize the strain experienced by the electronics, which are fabricated directly on the pillars' surface. In this design configuration, devices based on amorphous indium‐gallium‐zinc‐oxide can withstand different modes of deformation. Bending, stretching, and twisting experiments up to 6 mm radius, 20% uniaxial strain, and 180° global twisting, respectively, are performed to show stable electrical performance of the TFTs. Similarly, a fully integrated digital inverter is tested while stretched up to 20% elongation. As a proof of the versatility of mesa‐shaped geometry, a biocompatible and stretchable sensor for temperature mapping is also realized. Using pectin, which is a temperature‐sensitive material present in plant cells, the response of the sensor shows current modulation from 13 to 28 °C and functionality up to 15% strain. These results demonstrate the performance of highly flexible electronics for a broad variety of applications, including smart skin and health monitoring. Abstract : The fabrication of a mesa‐shaped flexible elastomeric substrate is reported. With this design configuration, the electronics, which are fabricated directly on the pillars' surface, can withstand different modes of deformation (bending, stretching, and twisting). These results demonstrate the performance of highly flexible electronic devices for a broad variety of applications, including smart skin and health monitoring.